24. THE EFFECTS OF FILIFORM NEEDLING AND ACUPRESSURE MASSAGE COMBINED WITH MOTOR THERAPY ON MOTOR FUNCTION REHABILITATION IN CHILDREN WITH SPASTIC CEREBRAL PALSY (Vietnam Journal of Community Medicine, 2025)
Objectives: Evaluation of the effectiveness of motor function rehabilitation in children with spastic cerebral palsy using filiform needling and acupressure massage combined with motor therapy at the National Hospital of Traditional Medicine.Subjects and methods: This study evaluated the effectiveness of motor function rehabilitation in children with spastic cerebral palsy using a combination of filiform needling, acupressure massage and physical therapy at the National Hospital of Traditional Medicine. 40 children aged 12-72 months, diagnosed according to the 1985 U.S criteria, received treatment at the Department of Internal Medicine - Pediatrics, National Hospital of Traditional Medicine. This was a pre-post clinical intervention without a control group. Patients were treated following the Ministry of Health’s protocol for 5 weeks.Results: Following the intervention, the mean total GMFM score increased significantly from 50.01 ± 14.05 to 73.01 ± 17.00 (p < 0.01). A notable improvement in the distribution of total GMFM scores was observed post-treatment compared to baseline. GMFM scores increased across all assessed motor milestones, with statistically significant differences at each milestone (p < 0.01). The most substantial improvement was recorded in the lying - rolling domain (26.53 points), followed by walking - jumping (25.3 points), standing (23.93 points), sitting (20.31 points), and crawling - kneeling (19.67 points).Conclusion: The combined treatment of traditional medicine and motor therapy is effective in improving motor function in children with spastic cerebral palsy.
Keywords: Filiform needling; acupressure massage; physical therapy; spastic cerebral palsy.